2018
DOI: 10.1021/acs.organomet.8b00635
|View full text |Cite
|
Sign up to set email alerts
|

Silylene Complexes of Late 3d Transition Metals Supported by tris-Phosphinoborate Ligands

Abstract: The complexes [BP3 R]­MX ([BP3 R] = PhB­(CH2­PR2)3 –, R = Ph, i Pr; M = Ni, Co, Fe; X = halide) were explored as platforms for generation of first-row metal silylene complexes. Direct silylation of [BP3 Ph]­NiCl or [BP3 iPr]­CoCl with (THF)2­LiSiH­Mes2 resulted in formation of the silylene complexes [BP3 Ph]­Ni­(μ-H)­(SiMes2) and [BP3 iPr]­Co­(μ-H)­(SiMes2), respectively. In contrast, [BP3 iPr]­FeBr reacted with (THF)2­LiSiH­Mes2 to produce the iron-alkyl [BP3 iPr]­Fe­(CH2-2-(Si­H2Mes)-3,5-Me2C6H2), a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…An examination of the C–C bond lengths in the phenyl ring and the NMR spectroscopic data confirmed an η 2 coordination mode. This η 2 -coordinated benzyl ligand serves as a three-electron donor and is similar to that observed in a previously reported nickel complex …”
Section: Results and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…An examination of the C–C bond lengths in the phenyl ring and the NMR spectroscopic data confirmed an η 2 coordination mode. This η 2 -coordinated benzyl ligand serves as a three-electron donor and is similar to that observed in a previously reported nickel complex …”
Section: Results and Discussionmentioning
confidence: 91%
“…This η 2 -coordinated benzyl ligand serves as a three-electron donor and is similar to that observed in a previously reported nickel complex. 21 For an initial comparison of the reactivity of the seven nickel catalysts, α-methylstyrene (2a) was chosen as a test substrate, primarily because substituted alkenes are recognized as inherently difficult substrates for hydrosilylation. 22 Reactions were performed in deuterated benzene for ease of monitoring with 1 H NMR spectroscopy.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The latter trend is well known for reactions of silanes with nickel complexes. [48][49][50][51][52] Exploration of potential energy surfaces revealed that numerous, slightly different, pathways give the same products. For these pathways, the intermediates and transition states differ by subtle changes in the structures of the NPN ligand, which can be folded or at and which can be k 3 -or k 2 -coordinated.…”
Section: Computational Studiesmentioning
confidence: 99%
“…3 J HP = 17.6 Hz, 3 J HH = 7.2 Hz, 6H, CH 3 ), 1.15 (dd, 3 J HP = 10.4 Hz, 3 J HH = 7.2 Hz, 6H, CH 3 ), 1.08 (dd, 3 J HP = 13.2 Hz, 3 J HH = 8.4 Hz, 6H, CH 3 ), 0.88 (dd, 6H, 3 J HP = 6.8 Hz, 3 J HH = 5.6 Hz, CH 3 ), −2.26 (dd, 1 J HP = 109.2, 5.6 Hz, 1 J PtH = 995.2 Hz, 1H, PtH). 13 (10). A 50 mL round bottom flask was charged with [(dippe)PtH] 2 (410 mg, 0.399 mmol), and the solid was dissolved in 10 mL of tetrahydrofuran (THF).…”
Section: Two Cationic Platinum Methyl Complexes [(Dippe)ptme-(oet 2 )...mentioning
confidence: 99%
“…Reactions of this type may be important in various metal-mediated transformations of silicon compounds or, more generally, in reactions involving the formal transfer of low-valent main group species. In particular, such processes have been implicated in catalytic reactions involving redistribution reactions of silanes (e.g., RSiH 3 to R 2 SiH 2 and SiH 4 ), silane dehydropolymerization, , and hydrosilylation. , This type of silylene transfer has been employed in the synthesis of a variety of neutral and cationic silylene complexes with metals from groups 6 through 9, ,, including the ruthenium complex [Cp*­(P i Pr 3 )­(H) 2 RuSiH­(R)] + (R = aryl) which is catalytically active for alkene hydrosilylations. , …”
Section: Introductionmentioning
confidence: 99%